2015
DOI: 10.1038/srep09520
|View full text |Cite
|
Sign up to set email alerts
|

Suberoylanilide Hydroxamic Acid Treatment Reveals Crosstalks among Proteome, Ubiquitylome and Acetylome in Non-Small Cell Lung Cancer A549 Cell Line

Abstract: Suberoylanilide hydroxamic acid (SAHA) is a well-known histone deacetylase (HDAC) inhibitor and has been used as practical therapy for breast cancer and non-small cell lung cancer (NSCLC). It is previously demonstrated that SAHA treatment could extensively change the profile of acetylome and proteome in cancer cells. However, little is known about the impact of SAHA on other protein modifications and the crosstalks among different modifications and proteome, hindering the deep understanding of SAHA-mediated ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 38 publications
(67 reference statements)
5
76
0
2
Order By: Relevance
“…So far, vorinostat (SAHA) in 2006 and romidepsin (depsipeptide, FK288) in 2009 have been approved by the US Food and Drug Administration (FDA) for the treatment of patients with cutaneous T cell lymphoma (CTCL) (Grant et al 2010; Mann et al 2007). It is reported that the profiles of acetylome and proteome were changed by HDACi treatment in NSCLC cells (Wu et al 2015; Wu et al 2013), suggesting that NSCLC cells are sensitive with HDACi. Furthermore, clinical trials have demonstrated that HDACis strongly enhance therapy efficacy of EGFR inhibitors (Gerber et al 2015) and platinum-based chemotherapy (Ramalingam et al 2010) in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…So far, vorinostat (SAHA) in 2006 and romidepsin (depsipeptide, FK288) in 2009 have been approved by the US Food and Drug Administration (FDA) for the treatment of patients with cutaneous T cell lymphoma (CTCL) (Grant et al 2010; Mann et al 2007). It is reported that the profiles of acetylome and proteome were changed by HDACi treatment in NSCLC cells (Wu et al 2015; Wu et al 2013), suggesting that NSCLC cells are sensitive with HDACi. Furthermore, clinical trials have demonstrated that HDACis strongly enhance therapy efficacy of EGFR inhibitors (Gerber et al 2015) and platinum-based chemotherapy (Ramalingam et al 2010) in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported that histone acetylation could induce the change of global proteome by epigenetics while non-histone acetylation of transcription factors could regulate proteome level through transcriptiome3233. Our classification was not clear enough to show the direct relationship among global proteome, acetylome and succinylome.…”
Section: Discussionmentioning
confidence: 68%
“…( A ) The analytical strategy and method for DCA-responsive quantitative profiling of global proteome, acetylome and succinylome in HCT116 cell line3334 (The Edraw Max V7.3 software is used to create the map in ( A ), https://www.edrawsoft.com/term-conditions.php). ( B ) Western blotting with anti-acetyl lysine antibody (up) and anti-succinyl lysine antibody (down).…”
Section: Figurementioning
confidence: 99%
“…HDAC inhibitors like suberoylanilide hydroxamic acid and romidepsin have been approved for the treatment of cutaneous T-cell lymphoma and chemical proteomics approaches have been used to study these inhibitors and their effect on specific HDAC complexes (Figure 2A) [79, 80, 81, 82]. Furthermore, proteomic approaches have been used to further study the effect HDAC inhibitors have on the proteome of a cell [95, 96]. The studies described here regarding the analysis of chromatin remodeling complexes and their relationship to cancer incorporate many, if not all, of the key sample preparation, quantitative proteomic analysis, and data analysis techniques and considerations described earlier in this review.…”
Section: Expert Commentarymentioning
confidence: 99%
“…A) Drug targeting enzymes like HDAC inhibitor suberoylanilide hydroxamic acid have been approved for the treatment of cutaneous T- cell lymphoma. Many proteomic studies, including AP-MS after drug treatment, have been used to study HDAC inhibitors and their effect on specific HDAC complexes, like Sin3/HDAC complexes [79, 80, 81, 82, 95, 96]. B) Drugs targeting specific modification readers like JQ1 small molecule BET bromodomain inhibitor have emerged as potentially powerful anticancer targeting drugs.…”
Section: Figurementioning
confidence: 99%